Perdebatan Perspektif Transisi dalam Kajian Kepemudaan - Oki Rahadianto Sutopo (Jurnal Studi Pemuda, 2022)
Artikel ini membahas mengenai perdebatan perspektif transisi dalam kajian kepemudaan. Dengan menggunakan studi pustaka, artikel ini menjelaskan empat hal yaitu terkait transisi berdasarkan umur vs dimensi sosiologis, terkait dengan dilema struktur-agensi, terkait dengan transisi vs generasi, relevansi interseksionalitas dalam kajian empiris transisi pemuda di Indonesia serta kemungkinan mewujudkan perspektif transisi yang berspirit dialog global. Penggunaan perspektif yang tunggal tidak memungkinkan dalam memahami transisi kaum muda Indonesia kontemporer. Hasil analisis dalam artikel ini justru mengusulkan mengenai pentingnya interseksi berbagai macam variabel baik kelas sosial, gender, spasial, generasi dan perubahan, serta aplikasinya dalam konteks sosio-kultural-historis yang baru. Dalam artikel ini juga dijelaskan mengenai pentingnya perspektif transisi melakukan kontekstualisasi pada pengalaman kaum muda Indonesia sebagai bagian dari Global South, memunculkan narasi-narasi kaum muda terpinggirkan dengan prinsip epistepraxis sekaligus membangun dialog dalam rangka membangun kesepahaman transisi kaum muda sebagai manifestasi dari generasi muda global. This article examines the debates of youth transition perspective in youth studies. Using library research, this article explores four aspects related to youth transition perspective: firstly, the debates between age cohorts and sociological dimension of transition; secondly, the dilemma between structure and agency; thirdly, ongoing debates between transition versus generations, and lastly, the relevance of intersectionality in the empirical studies of youth transition and its chance to develop youth transition with a spirit of global dialogue. In this article, I also argue that it is impossible to understand the complexities of youth transition only with one perspective as a tool of analysis. In contrast, I suggest on the importance of intersections between class, gender, spatiality, generation and social change as well as critical contextualisation in the new socio-cultural-historical context. In this article, I also suggest the importance of contextualisation of youth transition perspective based on the lifeworld of Indonesian youth as a part of Global South countries, raising the voices of marginalized youth using concept of epistepraxis, as well as set up dialogues in order to build understanding on the experiences of young people’s transition as a manifestation of global youth generation.